RAGAM REPRESENTASI IKLAN SENSUAL DI TELEVISI (KAJIAN SEMIOTIKA ROLAND BARTHES) - Ratu Nadya Wahyuningratna; Windhi Tia Saputra (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2018)
Electronic media has become a media that is effective enough to educate and provide information to the public, but if it is misused this medium can be a powerful medium to spread negative messages. The influence of television shows will be seen after the public receives messages from television. Today there are various types of shows on television but not all types of impressions have a good effect on the audience. There are several types of television shows that actually cause concern in the community because of wrong perceptions captured from television shows. For example, the existence of ad impressions that indulge the sensuality of women in the storyline. In this case, the advertisements in question are